Hukum Perlindungan Konsumen atas Barang yang Tidak Sesuai dengan Gambar pada Transaksi di Marketplace - Pratama Arief, Rifky (Universitas Ekasakti, 2023)
Marketplace is a place for online sellers; Despite having a good security system, there are still loopholes for fraud, one of which is by selling items that do not match the photo. This shows how difficult it is to be a buyer in buying and selling online. This research will discuss consumer legal protection against goods that do not match the image in transactions in the marketplace and the responsibility of business actors. This study used a normative juridical approach. Furthermore, the results of this study show that consumers have the right to get products according to the image, and sellers in the marketplace will be responsible for such errors according to the Consumer Protection Act. The marketplace can provide suggestions to sellers so that images of traded products can be depicted clearly.